(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
We empirically test the relationship between tourism performance and multiple tourism dimensions, namely, tourism Attractions (A), Basics (B), and Context (C). We test the Tourism A-B-C model using data from regions of Uzbekistan. The results serve to state out major trends, which focus on further research on this topic globally, and also they might be useful in diversifying interventions to improve the impacts in the tourism industry advancement.